SR-FTIR Biomolecular Characterization of the Hippocampus: The Role of Tenascin C in Adult Murine Neurogenesis in the Subgranular Zone - Milena Korenić; Andrej Korenić; Vera Stamenković; Tanja Dučić; Pavle Andjus (Cells)
To better understand adult neurogenesis, the biomolecular specificity of the subgranular zone should be investigated in comparison to other layers of the hippocampus. Adult neurogenesis occurs at a reduced rate in adulthood compared to the period of development, but it can be increased with exposure to an enriched environment (EE). This can be used to investigate the regulatory role of molecules present in the extracellular matrix, such as tenascin C (TnC). This study, using Synchrotron radiation Fourier Transform Infrared spectroscopy (SR-FTIR), shows that the differences between the hippocampal layers in adolescence are maintained as subtle and significant in adulthood. The main difference in FTIR spectra was observed for nucleic acid and carbohydrate and for the comparison of the subgranular zone (SGZ) with hippocampal CA3. Moreover, we have detected changes in the protein and nucleic acid content of the SGZ that accompany the process of neurogenesis under the influence of an enriched environment. The latter effects are, however, lacking in mice with a gene ablation for tenascin C. Overall, these results show that observed discrete biomolecular differences in hippocampal layers follow the rate of neurogenesis that is enhanced by EE and dependent on TnC.